Gestational choriocarcinoma presenting with uterine rupture and shock: a case report - Sharma, Vinutha M.; Babu, Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The aim of the study was to report an extremely rare case of gestational choriocarcinoma with a ruptured uterus, its early manifestations and management. With the patient's consent, her medical records were accessed, and older records, whichever were available, were retrieved from the hospital archives. A 24-year-old female presented with acute abdominal pain, distension and dyspnoea to the emergency department. The CT scan showed a massive haemoperitoneum of 1.5 l and a hyperechoic lesion in the fundus of the uterus. Given the previous history of complete molar pregnancy, gestational choriocarcinoma was suspected, and she was taken for an emergency laparotomy with hysterectomy. On opening the abdomen, a ruptured uterus with a dark brown exfoliative mass arising from the fundus of the uterus was found, and the whole specimen was sent for histopathologic examination. HPE confirmed that the tumour was choriocarcinoma, and based on the staging, the patient is being managed by gynaecology and medical oncology teams. Choriocarcinoma presenting as uterine rupture and shock is very rarely seen. Timely surgical intervention, transfusion of blood and blood products, followed by chemotherapy, can save a life.